Design and implementation of a virtual ARINC 653 simulation platform. (June 2021) - Chen, Jinchao; Chen, Keke; Du, Chenglie; Liu, Yifan
The ARINC 653 operation system is currently widely adopted in the avionics industry, and has become the mainstream architecture in avionics applications because of its strong agility and reliability. Although ARINC 653 can efficiently reduce the weight and energy consumption, it results in a serious development and verification problem for avionics systems. As ARINC 653 is non-open source software and lacks effective support for software testing and debugging, it is of great significance to build a real-time simulation platform for ARINC 653 on general-purpose operating systems, improving the efficiency and effectiveness of system development and implementation. In this paper, a virtual ARINC 653 platform is designed and realized by using real-time simulation technology. The proposed platform is composed of partition management, communication management, and health monitoring management, provides the same operation interfaces as the ARINC 653 system, and allows dynamic debugging of avionics applications without requiring the actual presence of real devices. Experimental results show that the platform not only simulates the functionalities of ARINC 653, but also meets the real-time requirements of avionics applications.